Review: The past, present and future challenges in epilepsy‐related and sudden deaths and biobanking. (20th February 2018) - Thom, M.; Boldrini, M.; Bundock, E.; Sheppard, M. N.; Devinsky, O.
Abstract : Awareness and research on epilepsy‐related deaths (ERD), in particular Sudden Unexpected Death in Epilepsy (SUDEP), have exponentially increased over the last two decades. Most publications have focused on guidelines that inform clinicians dealing with these deaths, educating patients, potential risk factors and mechanisms. There is a relative paucity of information available for pathologists who conduct these autopsies regarding appropriate post mortem practice and investigations. As we move from recognizing SUDEP as the most common form of ERD toward in‐depth investigations into its causes and prevention, health professionals involved with these autopsies and post mortem procedure must remain fully informed. Systematizing a more comprehensive and consistent practice of examining these cases will facilitate (i) more precise determination of cause of death, (ii) identification of SUDEP for improved epidemiological surveillance (the first step for an intervention study), and (iii) biobanking and cell‐based research. This article reviews how pathologists and healthcare professionals have approached ERD, current practices, logistical problems and areas to improve and harmonize. The main neuropathology, cardiac and genetic findings in SUDEP are outlined, providing a framework for best practices, integration of clinical, pathological and molecular genetic investigations in SUDEP, and ultimately prevention.